Reliability of lifeline networks with multiple sources under seismic hazard - Selcuk, A. Sevtap; Yucemen, M. Semih (2000)
Lifelines are networks extending spatially over large areas. Transportation systems, pipelines, communication and power transmission systems are examples of lifelines. The performance of a lifeline after a major earthquake is particularly vital for a community because of the emergency services that are usually required after such events. Performance measures are usually expressed in terms of quantities that are assessed based on statistical and probabilistic methodologies. The major performance measure is the probability of reaching from a specified point to another one successfull after a catastrophic event, such as an earthquake. Evaluation of this performance measure requires a seismic hazard methodology, capacity determination techniques and network reliability assessment methods. By combining these three aspects in one model, it is possible to calculate the reliability of any lifeline system under seismic danger. The aim of this paper is to present a probabilistic model for the evaluation of the seismic reliability of lifeline networks having multiple sources. The seismic reliability of a water distribution system located in Bursa, Turkey is assessed in order to show the implementation of the proposed model. The numerical calculations are carried out by the LIFEPACK software, which is developed for this purpose. - Reproduced
Keywords: Seismograms; Disasters; Natural disasters; Earthquake engineering